Chnical Guidance On Digital Waqf Land Registration Using The E-AIW Application For Wakif And Nazhir In Tasikmalaya City - Mubarok, Acep Zoni Saeful; Darmawan, Darwis; Saputra, Yuyus; Rahmat, Biki Zulfikri; Rakhmat, Anwar Taufik (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2024)
Waqf is frequently the source of family disputes that end up in court. The main reason of waqf conflicts is that waqf assets/land lack a proper legal form such as a Waqf Pledge Deed (AIW) from the Religious Affairs Office (KUA) or a Waqf Certificate from the National Land Agency (BPN). To receive the AIW, the community must manually register, which is a laborious process. To decrease bureaucracy, the Ministry of Religion has launched e-AIW, a digital waqf land registration application that will make it easier to receive the AIW. The current issue is that the application has only been disseminated to the KUA and has not reached the community directly owing to the unavailability. This service intends to provide technical guidance to the community on how to register waqf land via the e-AIW application. The method employed is delivery, practice with the e-AIW program, questions and answers, pre-test, and post-test. The outcomes of this technical guidance activity revealed a positive response from the participants. After being adequately led, participants' grasp of how to utilize the e-AIW application improved, as seen by the average post-test value of those who replied correctly, which was 89.4%. Furthermore, the findings of interviews with various participants revealed that this technical guidance gives a very simple way to utilize the e-AIW